Answer:
n = 3 / 2, and n = 2; Option C
Explanation:
We are given the following quadratic equation 2n^2 - 7n + 6 = 0, and must solve for the value of n;
2n^2 - 7n + 6 = 0 ⇒ Break this expression into groups,
( 2n^2 - 3n ) + ( - 4n + 6 ) = 0 ⇒ Factor n from 2n^2 - 3n,
n * ( 2n - 3 ) + ( - 4n + 6 ) = 0 ⇒ Factor - 2 from - 4n + 6,
n * ( 2n - 3 ) - 2 * ( 2n - 3 ) = 0 ⇒ Factor out common term 2n - 3,
( 2n - 3 )( n - 2 ) = 0 ⇒ Solve through the Zero Factor Principle,
2n - 3 = 0, and n - 2 = 0 ⇒ Solve for n,
Solution; n = 3 / 2, and n = 2